2022
DOI: 10.1155/2022/4894922
|View full text |Cite
|
Sign up to set email alerts
|

Chimp Optimization Algorithm to Optimize a Convolutional Neural Network for Recognizing Persian/Arabic Handwritten Words

Abstract: Handwritten character recognition is an attractive subject in computer vision. In recent years, numerous researchers have implemented techniques to recognize handwritten characters using optical character recognition (OCR) approaches for many languages. One the most common methods to improve the OCR accuracy is based on convolutional neural networks (CNNs). A CNN model contains several kernels accompanying with pooling layers and nonlinear functions. This model overcomes the problem of adjusting the value of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Authors have found that DenseNet is more suitable for a Persian OCR system because it has less learnable parameters which makes it less prone to overfitting. Another usage of a well known CNN-based network in Persian OCR system can be found in [38] where authors have used a LeNet [39] optimized by meta heuristic training in their system. Authors have utilized four algorithms of firefly algorithm, ant colony optimization, chimp optimization algorithm (ChOA), and particle swarm optimization to optimize LeNet's weights and concluded that ChOA serves this purpose better than the other algorithms.…”
Section: Persian Languagementioning
confidence: 99%
“…Authors have found that DenseNet is more suitable for a Persian OCR system because it has less learnable parameters which makes it less prone to overfitting. Another usage of a well known CNN-based network in Persian OCR system can be found in [38] where authors have used a LeNet [39] optimized by meta heuristic training in their system. Authors have utilized four algorithms of firefly algorithm, ant colony optimization, chimp optimization algorithm (ChOA), and particle swarm optimization to optimize LeNet's weights and concluded that ChOA serves this purpose better than the other algorithms.…”
Section: Persian Languagementioning
confidence: 99%
“…Deep Learning has had a huge impact on handwriting recognition applications in different languages as well as on Persian handwritten recognition [23,24,25,26,27,28]. Here deep models are trained using the words, letters, and digits in the Khayyam dataset.…”
Section: Deep Neural Networkmentioning
confidence: 99%